Nanobionics for sustainable crop production: Recent development to regulate plant growth and protection strategies from pests - Rakesh Bhaskar; Surya Prakash Pandey; Umesh Kumar; Hyunjin Kim; Santhosh Kumar Jayakodi; Mukesh Kumar Gupta; Sung Soo Han (Elsevier, 2024)
The interface between nanostructured materials and plant cell organelles, such as chloroplasts, and has been recently found to have potential to impart organelles with new functions and enhanced performances. The plant nanobionics-based technologies can be implemented to provide the precise quantity of nutrients and pest control systems to improve the crop productivity as the concerns are growing regarding various agricultural difficulties such as poor nutrient use, stagnant yields, nutrient deficiencies, climate change, and water scarcity. The creation of novel nanomaterial (NM) based-fertilizers and -pesticides has encouraged the assimilation of mineral nutrients as well as to control pests without harming the environment. These nanostructured materials are more effective in releasing nutrients in a site-specific manner, increasing plant uptake efficiency and decreasing nutrient loss, and targeting specific pests than conventional fertilizers and pesticides. This article discusses about recent advancement of innovative nanostructured materials that could transport nutrients, such as carbon-based nanoparticles (NP) and metal-based NP: Iron (Fe), Copper (Cu), Zinc (Zn), Silver (Ag), and Cerium (Ce) etc. We explored the potential development and implementation challenges for these NPs in this article and highlighted the importance of using a systems approach when creating nano bionics-based technology in the near future.